MDCT and MRI of the Heart - De Cecco, Carlo Nicola. (A-Z Notes in Radiological Practice and Reporting, 2014)
The new series A-Z Notes in Radiological Practice and Reporting provides practical guides for residents and general radiologists, organized alphabetically, primarily according to disease or condition. All booklets are designed so as to comprise only a small number of illustrations and to cover a large spectrum of topics referring to different anatomical regions of interest. The first volume on cardiac CT and MR imaging contains all the practical suggestions that can help a radiologist in the execution and reporting of a cardiac examination. The book is structured to offer an easy and fast consultation on cardiac imaging and pathology with the use of tables and figures. Entries typically include a short description of pathological and clinical characteristics, guidance on selection of the most appropriate imaging technique, a schematic review of potential diagnostic clues, and useful tips and tricks.